Fabrication of double crosslinked chitosan/gelatin membranes with Na+ and pH dual-responsive controlled permeability. (15th May 2020) - Liu, Jin; Wang, Shunyi; Xu, Ke; Fan, Zaibi; Wang, Panpan; Xu, Zijun; Ren, Xueqin; Hu, Shuwen; Gao, Zideng
Highlights: A doubly crosslinked, dual-responsive chitosan/gelatin film has been prepared. Genipin and potassium pyroantimonate are used as covalent and ionic crosslinkers. The film shows controlled-release behavior with pH- and Na + -responsive permeability. Urea and plant hormone release tests show the practical applicability of the film. Abstract: A double crosslinked membrane based on chitosan/gelatin with controlled release properties was synthesized in aqueous system using potassium pyroantimonate and genipin as the ionic crosslinker and covalent crosslinker, respectively. The membranes were characterized using FT-IR, UV–vis spectra, and SEM. In addition, the thermal stability, contact angle, mechanical and controlled release properties were measured. Double-crosslinking significantly improved the hydrophobicity, thermal stability, and tensile strength of the membrane. The permeabilities of various plant nutrients, including urea and plant growth regulators (PGRs), were evaluated. Under the optimized conditions, the lowest flux (J) of urea was 2.89 mg/ (cm 2 ·h). Urea and PGR release were sustained for up to 3 and 10 days, respectively. The release of agrochemicals in this study followed the Weibull model, demonstrating the Na + -responsive and pH-responsive permeability of the films. This dual-responsive film has potential applications in salinized barrier soil, water treatment, separations, and other membrane applications.